Mechanism of Trust Instrument in the Islamic Wealth Management at Amanah Raya Berhad ‎Malaysia: an Analysis Study - Awang, Abdul Bari; Abdullah , Muhamad Muizz; Zakaria , Mohamad Sabri (International Journal of Al-Turath In Islamic Wealth and Finance, 2023)
Managing assets during life in a disorderly manner will lead to complicated planning, and there is no denying that this is one of the reasons that contributed to the unclaimed money reaching the value of 70 billion in 2020. Thus, this study aims to find out the implementation of a trust instrument in Amanah Raya Berhad, which is a Public Trustee in Malaysia for the estate administration. This study used three methodologies: first: inductive by examining the jurist opinions on Islamic entrustment (al-wiṣāyah) such as referencing the Fiqh Books, Malaysia Civil Law, and article journals on trust instrument. Second: analysis and descriptive by analyzing all the information obtained in detail, describing the execution of the trust, and explaining the extent of the potential trust in the estate administration. Furthermore, interviews were also conducted with several officers at the company. This study found that trust is one of the most important instruments in the Muslim estate administration. Finally, this study views that trust instruments should be executed immediately for the benefit of the beneficiary and their future.